Contribution of Methane Benthic and Atmospheric Fluxes of an Experimental Area (Sitka Stream). Issue 8 (19th May 2015) - Bednařík, Adam; Čáp, Lubomír; Maier, Vítězslav; Rulík, Martin
<x xml:space="preserve">Abstract</x> Contributions of methane benthic fluxes and methane emissions to the total methane amount were studied during the summer season for two consecutive years. Considering the fact that methane is produced in great amount within hyporheic sediments, we have expected that both methane released by the benthic fluxes into the overlying water and methane emitted to the atmosphere should significantly affect the total methane budget of the stream water within the experimental area. In order to asses this assumption, we measured methane concentrations within the vertical sediment profile of a hyporheic zone, direct benthic methane fluxes by static chambers, methane concentrations in the surface water, and methane emissions into the atmosphere simultaneously. The methane concentrations in interstitial water tended sharply to increase with sediment depth (0.54–734.99 μmol L−1) and were strongly correlated with benthic fluxes (r = 0.88, p < 0.05). We also found a considerable variability in the benthic methane fluxes (0–12.59 mmol m−2 day−1) and the spatial variability (0–71.43%) of the experimental area, suggesting that there may be various factors that affect the rate of benthic fluxes including methanotrophy in the top sediment layers. Generally, the contribution of benthic fluxes and methane emissions to the methane budgets of the experimental area was negligible (0.034 (0.45%) and 0.074 mol day−1 (0.98%), respectively).